Neurochemical Phenotype of Reelin Immunoreactive Cells in the Piriform Cortex Layer II - Carceller, Hector; Rovira-Esteban, Laura; Nacher, Juan; Castrén, Eero; Guirado, Ramon (Frontiers in Cellular Neuroscience, 2016)
ABSTRACT Reelin, a glycoprotein expressed by Cajal-Retzius neurons throughout the marginal layer of developing neocortex, has been extensively shown to play an important role during brain development, guiding neuronal migration and detachment from radial glia. During the adult life, however, many studies have associated Reelin expression to enhanced neuronal plasticity. Although its mechanism of action in the adult brain remains mostly unknown, Reelin is expressed mainly by a subset of mature interneurons. Here, we confirm the described phenotype of this subpopulation in the adult neocortex. We show that these mature interneurons, although being in close proximity, lack PSA-NCAM expression, a molecule expressed by a subpopulation of mature interneurons, related to brain development and involved in neuronal plasticity of the adult brain as well. However, in the layer II of Piriform cortex there is a high density of cells expressing Reelin whose neurochemical phenotype and connectivity has not been described before. Interestingly, in close proximity to these Reelin expressing cells there is a numerous subpopulation of immature neurons expressing PSA-NCAM and DCX in this layer of the Piriform cortex. Here we show that Reelin cells express the neuronal marker NeuN, but however the majority of neurons lack markers of mature excitatory or inhibitory neurons. A detail analysis of its morphology indicates these that some of these cells might correspond to semilunar neurons. Interestingly, we found that the majority of these cells express TBR-1 a transcription factor found not only in post-mitotic neurons that differentiate to glutamatergic excitatory neurons but also in Cajal-Retzius cells. We suggest that the function of these Reelin expressing cells might be similar to that of the Cajal-Retzius cells during development, having a role in the maintenance of the immature phenotype of the PSA-NCAM/DCX neurons through its receptors ApoER2 and VLDL in the Piriform cortex layer II during adulthood.